Gas Diffusivity‐Based Design and Characterization of Greenhouse Growth Substrates. Issue 3 (2nd August 2013) - Chamindu Deepagoda, T.K.K.; Moldrup, Per; Tuller, Markus; Pedersen, Mette; Chen Lopez, Jose Choc; Wollesen de Jonge, Lis; Kawamoto, Ken; Komatsu, Toshiko
Abstract : Growing plants in containerized substrates has long been common practice in horticulture. Containerized plants (e.g., greenhouse tomatoes) have restricted access to essential growth resources such as oxygen, water, and nutrients. Since a wide range of inorganic and organic materials, and different combinations thereof, are commonly used as growth media, detailed and comparable physical characterization is key to identify the best performing media. In this study, five potential growth media and two mixtures thereof were characterized based on soil gas diffusivity ( D p / D o, where D p and D o are gas diffusion coefficients in soil air and free air, respectively) and an operationally defined critical window of diffusivity (CWD) representing the interval of air‐filled porosity between critical air filled porosity where D p / D o ≈ 0.02 and interaggregate porosity. The D p measurements were conducted with 100‐cm 3 samples from wet to complete dry conditions achieved by stepwise air drying and equilibration of initially water‐saturated samples. A previously developed inactive pore and density‐corrected (IPDC) model was able to describe gas diffusivities for media with distinct inactive pore space in the interaggregate pore region reasonably well. An extended IPDC model was introduced for media exhibiting a second percolation threshold in the intra‐aggregate pore region. The analysis revealed comparable CWD values for the majority of the investigated media. The results further highlighted the importance of other major aspects (physical, chemical, and biological) of growth media characterization for optimal growth media design. A simple approach toward designing a gas diffusivity mixing model is presented to assist with selection of optimal mixing ratios of growth media with markedly different D p / D o behavior.